Scientific production about the elderly with dementia in the health primary care (Research, Society and Development, 2020)
Objective: synthesize the scientific production on primary health care assistance for the elderly with dementia. Results: As for the subjects of the studies, the majority addresses aspects related to the diagnosis (n = 6), followed by professional performance (n = 2), disease management (n = 2) and approaching the family and caregivers. As for the characterization of the sample (n = 11), they are in English (n = 5) and Portuguese (n = 6), mostly as a literature review (n = 6), elaborated mainly in the American continent (Brazil = 5). Final considerations: There is still a lot to be researched and asked to bring about the appropriate improvements on the assistance to the elderly with dementia in primary care, mainly in relation to the integrality of care and the insertion of the multidisciplinary team.